Perencanaan dan Pembuatan Mobile Apps Informasi dan Prediksi Harga Emas dalam Rupiah melalui Agregasi Harga Emas dan Kurs Dollar - Stella Wiedjarnarko; Rolly Intan; Alexander Setiawan (Jurnal Infra, 2018)
Gold is one of the assets that is popular amongst people on many of its aspects ranging from its profitability in investing or saving to its beauty as a jewelry. Its ever increase in demand that exceeds the existing supply causes an instability in its price. This phenomenon disturbs the balance in market causing parties of interest to lose security on buying gold in the near future.This research introduces a solution using a mobile application to aid in decision making by providing prediction of the gold price in rupiahs using parameters necessary in Bloomberg site (www.bloomberg.com), FX Empire site (https://www.fxempire.com), 30rates site (http://30rates.com) and Longforecast site (https://longforecast.com). An aggregate function and moving average will be used to get the necessary data which will then be delivered in a simple and easily accesed user interface.The testing results shows that aggregate function and moving average are a viable method to calculate the prediction data of the gold price.